Penggunaan Jenis Pembalut Berhubungan dengan Kejadian Keputihan - Mayasari, Windatania; Taribuka, Nety; Zubaedah, Zubaedah; Warhangan, Hawa (Jurusan Kebidanan Poltekkes Kemenkes Mamuju, 2021)
The use of pantyliner is one of the causes of vaginal discharge because pads use dangerous chemicals for the bleaching process, which produce dioxins that can trigger vaginal discharge. This study aims to determine the relationship between the use of sanitary napkins during menstruation in SMA. This study used a cross sectional approach. The population in this study were 144 high school students, the sample in this study were 105 female students. The sampling technique used was proposive sampling. Data collection was done by using questionnaires and forms related to data recording. Bivariate analysis using the chi squre statistical test. 105 respondents using herbal sanitary napkins in the highest normal incidence was 35 (70%) and the lowest normal use of abnormal sanitary napkins was 12 (21.8%). The incidence of abnormal vaginal discharge in ordinary sanitary napkins 55 (100%) and the incidence of vaginal discharge in 50 (100%) herbs napkins. There was a relationship between the use of this type of pantyliner and the incidence of flour albus in SMA, Waplau Subdistrict, Buru Regency.